Monte Carlo Simulation of the Gamma-Ray Transmissions for the newly Designed Shielding Blocks used in Radiotherapy - Nuray Yavuzkanat; Hazal Burcu Saraç Kürem (Journal of Advanced Research in Natural and Applied Sciences)
Radiotherapy is one of the most important treatment methods of cancer, which is the worldwide disease nowa-days. It is essential to protect the critical organs and healthy tissue inside the radiated area during the radiotherapy. For this reason, Cerrobend block (lipowitz alloy), which is made specifically for each patient, are commonly used in the hospitals. In the clinical application, the acceptable level of the gamma-ray transmission for Cerrobend blocks must be less than 5%. In this research, GEANT4 based GATE simulation program modelled to compare between gamma-ray transmissions of the standard Cerrobend block and newly designed Cerrobend blocks formed by adding the various number of the pure lead marbles. Experimental measurements were carried out with Alcyon II model Co-60 teletherapy machine for various field sizes by using Farmer type 0,6 cc ion chamber, PTW Unidos Dosimeter and solid phantom in Dr. Abdurrahman Yurtaslan Ankara Oncology Training and Research Hospital in 2010. The gamma-ray transmission of the newly designed Cerrobend block was found less than the standard block, therefore the protection of the critical organs for the patient could be better. The dose acquired by GEANT4 based GATE simulation program is consistent in experimentally measured radiation dose. Furthermore, the values of the linear attenuation coefficient theoretically obtained from XCOM software agree with the values acquired by experiment and simulation